Morbidity Milestones Demonstrate Long Disability‐Free Survival in Parkinson's Disease Patients with Deep Brain Stimulation of the Subthalamic Nucleus. Issue 4 (28th February 2023) - Schnalke, Nils; Konitsioti, Agni; Frank, Anika; Kurz, Martin; Polanski, Witold H.; Themann, Peter; Wolz, Martin; Sobottka, Stephan B.; Reichmann, Heinz; Falkenburger, Bjoern; Klingelhoefer, Lisa
ABSTRACT: Background: Deep brain stimulation of the subthalamic nucleus (STN‐DBS) is an effective treatment for Parkinson's disease (PD). The long‐term benefit in PD patients with STN‐DBS in comparison to medical treatment (MT) alone has not yet been demonstrated conclusively. Objectives: To judge the long‐term outcome of patients with STN‐DBS. Methods: To assess the evolution of PD symptoms and health‐related quality of life (HRQoL) after deep brain stimulation (DBS) surgery, we conducted a cross‐sectional analysis of 115 patients with STN‐DBS with rater‐based scales and self‐reported questionnaires. In addition, we screened records of all our STN‐DBS patients (2001–2019, n = 162 patients) for the onset of the morbidity milestones (falls, hallucinations, dementia, and nursing home placement) to assess disability‐free life expectancy. Results: In the first year of STN‐DBS, levodopa equivalent dose was reduced and motor function improved. Nonmotor symptoms and cognition remained stable. These effects were similar to previous studies. Morbidity milestones occurred 13 ± 7 years after diagnosis. Motor function, cognition, and HRQoL significantly worsened after the occurrence of any milestone, confirming the clinical relevance of these milestones. After onset of the first milestone, mean survival time was limited to 5 ± 0.8 years, which is comparable with patients with PD but without STN‐DBS. Conclusions: On average, PD patients with STN‐DBS live with their disease for a longer time, and morbidity milestones occur later in the disease course than in PD patients with MT. As judged by morbidity milestones, morbidity remains compressed into the final 5 years of life in PD patients with STN‐DBS.